Leopardi: gli errori popolari e i pregiudizi degli antichi - Cherchi, Paolo (Rivista Internazionale di Studi Leopardiani, 2022)
In his Saggio sopra gli errori popolari degli antichi Leopardi disclaims any debt to some scholars who before him have dealt with the “popular mistakes”. He differs from them and establishes a difference between error and prejudices. The latter ones determine how the ancients saw reality, and they nourished their phantasy and poetic language, which save men from the dreadfulness of the “raison”.